Pros and Cons of COVID-19 Vaccines. - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2023)
We are faced with a typical flu of the winter season, identical to many others we have known in the past. The only difference is that it is not a flu virus, but COVID, but this does not justify the media terror that has spread. On the other hand it is now established that for certain types of influences from covid it is enough to resort to oral antiviral therapies. The variant that is circulating today is the same that circulated in Africa when it was summer here, without serious consequences. The Africans themselves denied Western alarmism, saying that what was happening exaggerated in portraying the South African variant as dangerous. The efficacy of vaccines against the COVID-19 subsided after the delta variant became predominant. The efficacy of the vaccines above 65 years of age with messenger RNA has remained high in the sense of their protection against the hospitalization. New variants seem to avoid the immune response and show signs of spreading more rapidly. Some data seem to indicate that the new omicron variant may be milder, but all the same will lead to one plethora of hospital admissions. Betacoronavirus infection induces strong and long-lasting immunity of T lymphocytes to proteins structural and CD4 and CD8 T cells were recognized in all convalescents who recognized multiple regions of nucleocapsid protein (NP). The unvaccinated person runs no risk if he maintains a normal hygiene profile. The vaccinated with RNA messenger vaccines can be a vehicle of contagion as long as he produces the first antibodies since it could be already infected with any of the 4 benign human coronaviruses and therefore replicate the vaccine received before to produce the specific antibodies that will allow him to be immune to Covid-19 until the duration of at least twelve months from the first administration. In the case of vaccination with adenovirus vaccine as a vector and the spike protein carrier gene, no danger for the unvaccinated cohabitant. Since young people have their own immunological response towards this epidemic from COVID-19, it is enough not to create the storm of interleukins of adults and the elderly, in regards by the same agent. Therefore their vaccination is almost useless also because recent American studies report the possibility of myocarditis and other damages.